2019
DOI: 10.1177/0194599819887096
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Pediatric Tracheostomy and Risk Factors for Poor Outcomes: An 11‐Year Single‐Center Experience

Abstract: Objective Children with long-term tracheostomies are at higher risk of complications. This study aims to describe the epidemiology, outcomes, and factors associated with successful decannulation in children undergoing tracheostomy. Study Design Case series with chart review. Setting Tertiary hospital. Subjects and Methods A retrospective analysis was conducted on pediatric tracheostomies performed from 2006 to 2016. Demographics, preexisting comorbidities, indications for tracheostomy, and pretracheostomy vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 22 publications
3
31
0
1
Order By: Relevance
“…Despite the high degree of complexity of the patient population, in-hospital mortality rates are consistent with previous studies on pediatric tracheostomy. 9,31,32 As expected, complex patients were significantly more likely to die during their index admissions than non-complex patients (OR = 11.6, 95% CI: 1.5-91.3, P < .02). Complex patients in this population were younger, which is consistent with previous reports that neonates and infants with tracheostomies are at highest risk of mortality among all pediatric patients.…”
Section: Discussionsupporting
confidence: 65%
“…Despite the high degree of complexity of the patient population, in-hospital mortality rates are consistent with previous studies on pediatric tracheostomy. 9,31,32 As expected, complex patients were significantly more likely to die during their index admissions than non-complex patients (OR = 11.6, 95% CI: 1.5-91.3, P < .02). Complex patients in this population were younger, which is consistent with previous reports that neonates and infants with tracheostomies are at highest risk of mortality among all pediatric patients.…”
Section: Discussionsupporting
confidence: 65%
“…The reported decannulation rate in children varied from 23 to 70%. 2 , 4 , 18 , 27 Similar to our study, Zank et al reported a higher rate of successful decannulation in UAO and trauma cases. 22 On the contrary, Canning et al reported UAO as high risk for unsuccessful decannulation.…”
Section: Discussionsupporting
confidence: 90%
“…It seems that the average age at the time of tracheostomy in different studies depended on the most frequent indication. 25 Younger age-group was reported in studies in which UAO, craniofacial anomalies, and cardiac diseases were predominant indications 4 , 18 while older age >3 years was observed in studies when neurological impairment was the cause in the majority of children. 23 , 24 A similar observation was present in our study and by Lin et al 24 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations